The Effect of Teacher Communication Through Storytelling Method on the Creativity Level of Kindergarten Students in Bekasi City - Afrina Sari; Hermansyah Hermansyah (International Journal of Emerging Issues in Early Childhood Education, 2022)
Background - Children's creativity can be increased through learning methods. Creativity in kindergarten student learning aims to develop students' curiosity and develop their imagination. It is suspected that teacher communication in telling a story using the storytelling method will help increase student creativity in Kindergarten in the city of Bekasi. Purpose – This study aims to: 1) analyze the effect of teacher communication variables on the creativity level of kindergarten students in Bekasi City. 2) analyze the storytelling method variable as a mediator variable between teacher communication and students' creativity level. Design/methodology/approach – The research method uses the quantitative-correlation method, namely calculating the relationship between variables using the SPSS application and the Sobel calculator to calculate the mediator variable, whether it can be used as a mediator variable after being calculated by using a Sobel calculator. The population of this study was kindergarten students in Bekasi City who were taken randomly. The research sample was determined in kindergarten schools using the storytelling method as a learning method. Randomly selected, namely private kindergarten "Islam Mentari" and Islamic kindergarten "Gema Nurani". Of the two kindergartens, the respondents were parents of students from the two kindergartens. as many as 60 parents of students, namely 30 parents of Mentari Islam students, and 30 parents of "Gema Nurani" students.. Findings – The results showed 1) there was an influence of teacher communication variables on the creativity level of kindergarten students in Bekasi City. The value of R = 0.381, and R² = 0.145, so it can be said that teacher communication contributes to the storytelling method by 14.5%. This means that there is an influence of teacher communication of 14.5%, and the remaining 85.5% is influenced by other variables not examined in this study 2) there is an effect of teacher communication on the level of creativity of students, and the storytelling method as a mediator is significant at the level of p = 0.05. Results of the Sobel Calculator calculation, can be explained that the Sobel test value is test statistic value = 2.080, standard error value = 0.090, P-value = 0.038. it can be seen that the value is 2,080 > p-value = 0.038, meaning that the Sobel Test calculation shows a significant level of = 0.05, indicating that the Storytelling method can be a mediator variable. This means that the test results show that the storytelling method can be a mediator variable in research between teacher communication variables and students' creativity levels. Limitations– there are limitations of researchers when taking data into the field, then it is done using google form. In addition, the limitations of this study were that it was conducted in kindergarten schools in 2 private kindergartens.. Originality/value – This research can be trusted as the researcher's original research and case selection in kindergarten schools using the storytelling method